Motorcycle alarm system using RFID technologies / Muhammad Fikri Zaharudin, Muhammad Zulkifli Bidi and Yushaida Aminudin - Zaharudin, Muhammad Fikri; Bidi, Muhammad Zulkifli; Aminudin, Yushaida (2015)
The theme for this final years project is safety and healthy. Beside that, choose to make a motorcycle security system using RFID technology. This project are design to prevent motorcycle from been stolen by thief. Moreover, with this project we would like to decrease of motorcycle crime thief rates in this country. This project is combination of RFID circuit with alarm circuit that are design in Proteus software. This project aims for the bike user in order to avoid their bikes stolen, and as precautionary measure in case. With the RFID and alarm in motorcycle system, it will be difficult for thief from stealing motorcycle. For the expecting this project can achieve the project objective and become one of the important things to bikers